PENGELOLAAN LIMBAH BUNGA PACAR AIR (IMPATIENS BALSAMINA) DARI CANANG SARI DAN PENETAPAN WAKTU PENGUMPULAN - Audina Setya Fitriana; Edia Rahayuningsih; Rochim Bakti Cahyono (Fakultas Teknologi Lingkungan dan Mineral - Universitas Teknologi Sumbawa, 2025)
The aims of this research are 1) to develop system for collection and separation of flower waste in area model; 2) to analyse the natural dye content in pacar air flower waste during the collection and drying process. The data was collected by interviewing, giving questionnaire, and observing. Respondents in this research were staff of the environmental authority and communities in 5 sub-districts at Buleleng regency. From results of questionnaire, the current behaviour of community in managing canang sari waste can be identified. Then, it can be used as basis for preparation of an effective canang sari waste collection system and qualified as natural dye raw-material. To determine the quality of flowers for collection time, natural dye extraction from pacar air flower waste was carried out at various collection times. Duration of observation time: 1-7 days after canang sari used for worship. Analysis of natural dye content in extract with several tests, used phytochemical, gravimetry, and UV-vis spectrophotometry. The conclusion that can be drawn is that flower waste collection system is carried out in two categories of locations, at places of worship and non-places of worship. Collection time is every 2 days, with the flower waste will be puchased. Sorting system is carried out by providing blue bins for flower waste and grey bins for other waste. Flower waste collected every 2 days, produces the highest natural dye content compared to other collection times, at 59.0481% grams of dye per gram of dried flowers, with anthocyanin content at 32.06185 mg/l.